2014
DOI: 10.1002/humu.22637
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Trinucleotidic Repeats During Chromatin Remodeling in Spermatids

Abstract: Transient DNA breaks and evidence of DNA damage response have recently been reported during the chromatin remodeling process in haploid spermatids, creating a potential window of enhanced genetic instability. We used flow cytometry to achieve separation of differentiating spermatids into four highly purified populations using transgenic mice harboring 160 CAG repeats within exon 1 of the human Huntington disease gene (HTT). Trinucleotic repeat expansion was found to occur immediately following the chromatin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…the increase of CAG repeat length in lymphocytes over time similar to that of sperm, which has not been reported in prior reports [29]. Additionally, the discrepancy between studies in rodent models and human HD patients, especially in sperm, could be due to the fundamental differences in spermatogenesis that impact CAG repeat instability in HD [16,19,[30][31][32]. Rodent goes through many developmental stages (19 steps) with multiple replication steps resulting in 10 times more sperm production compared to humans, while human only undergoes 6 developmental stages [30].…”
Section: F Clever Et Al / Longitudinal Study On Cag Instability In mentioning
confidence: 82%
“…the increase of CAG repeat length in lymphocytes over time similar to that of sperm, which has not been reported in prior reports [29]. Additionally, the discrepancy between studies in rodent models and human HD patients, especially in sperm, could be due to the fundamental differences in spermatogenesis that impact CAG repeat instability in HD [16,19,[30][31][32]. Rodent goes through many developmental stages (19 steps) with multiple replication steps resulting in 10 times more sperm production compared to humans, while human only undergoes 6 developmental stages [30].…”
Section: F Clever Et Al / Longitudinal Study On Cag Instability In mentioning
confidence: 82%
“…Flow sorted spermatids obtained as described here can be used for a variety of experiments. DNA from these cells can easily be extracted using commercial genomic DNA purification kits and demonstrated to be of proper quality for PCR analyses 9 and next generation sequencing (data not shown). Sorted spermatids can also be used for protein analyses 9 where we performed several immunoblots against stage-specific markers to confirm the high purity of the sorted spermatids.…”
Section: Discussionmentioning
confidence: 99%
“…DNA from these cells can easily be extracted using commercial genomic DNA purification kits and demonstrated to be of proper quality for PCR analyses 9 and next generation sequencing (data not shown). Sorted spermatids can also be used for protein analyses 9 where we performed several immunoblots against stage-specific markers to confirm the high purity of the sorted spermatids. We verified the cellular integrity of the sorted spermatids and found that the nucleus and cytoplasm of all populations remain intact.…”
Section: Discussionmentioning
confidence: 99%
“…For HD, which has a paternal bias for inheritance of expanded alleles, an illuminating study of repeat size in human male spermatocytes concluded that the majority of expansions occur as a pre-meiotic event, although some additional expansions were observed to occur post-meiotically (Yoon et al ., 2003). Yet in a mouse model of HD, it was concluded that most expansions arise after meiosis in the haploid gamete (Kovtun & McMurray, 2001), and recent results indicate that these post-meiotic expansions arise during remodeling of spermatid chromatin (Simard et al ., 2014). A factor that could explain the difference between the mouse and human data is that the human spermatogonial cells studied were estimated to have undergone many more cell divisions (~600–800 over 40 years) compared with those in the mice (~35 over <3 months).…”
Section: Repeat Expansions Cause Human Diseasementioning
confidence: 99%